2022
DOI: 10.1002/maco.202112931
|View full text |Cite
|
Sign up to set email alerts
|

Isothermal short‐term oxidation behavior of MAR‐M246 nickel‐based superalloy at 800°C and 1000°C

Abstract: Superalloys are widely employed at high temperatures for structural applications. Hence, knowledge about the oxidation of these materials is essential.However, the literature is scanty when it comes to some families of superalloys. The purpose of this study was therefore to analyze the MAR-M246 polycrystalline alloy in isothermal short-term tests at 800°C and 1000°C for up to 240 h. Thermodynamic simulations were performed to evaluate the material's phase stability as a function of temperature and to assess th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 21 publications
0
0
0
Order By: Relevance
“…Figure 8a,b show the composition for MC carbides for both MAR-M246(Ta) and MAR-M246(Nb), respectively. These images suggest that the MC carbide is mainly formed by Ta, Nb, Ti, and W. This result converges with the information exhibited in previous studies [14,25]. Comparing these two superalloys, it can be observed that the at% of Ta and Nb in MC carbides are similar in the respective alloys.…”
Section: Thermodynamic Simulationssupporting
confidence: 90%
See 3 more Smart Citations
“…Figure 8a,b show the composition for MC carbides for both MAR-M246(Ta) and MAR-M246(Nb), respectively. These images suggest that the MC carbide is mainly formed by Ta, Nb, Ti, and W. This result converges with the information exhibited in previous studies [14,25]. Comparing these two superalloys, it can be observed that the at% of Ta and Nb in MC carbides are similar in the respective alloys.…”
Section: Thermodynamic Simulationssupporting
confidence: 90%
“…It can be justified by the high content of the primary elements that constitute the alloys (Co, W, and Ni, as can be seen in Table 1) and also by the absence of O. Similar results were found in previous papers [13,25]. Baldan et al [25] also observed spalled areas for the conventional MAR-M246 exposed for isothermal oxidation tests at 1000 • C for 240 h. Additionally, Alkmin et al [13] found spalled areas for MAR-M246(Nb) pseudo-isothermally tested at 1000 • C for 650 h. Figure 5 shows the cross-section SEM/EDS analysis for the two superalloys oxidized for up to 180 cycles at 1000 °C.…”
Section: Topographic and Cross-section Sem/eds Analysissupporting
confidence: 88%
See 2 more Smart Citations